Introduction: Posting of Workers – Company Profiles, Access to Information, and Rule Compliance - Danaj, Sonila (Two Homelands, 2025)
This special thematic section explores and provides new evidence at the nexus between company profiles, access to information, and rule compliance. The three articles of the special thematic section are based on research conducted in the frame of the transnational research project titled “Assessment of the channels of information and their use in the posting of workers” (INFO-POW), co-funded by the European Commission and implemented in Austria, Belgium, Italy, Slovakia, and Slovenia during 2022–2024.